Optimization of Human Resources and Utilization of Information Technology in Driving the Digital Economy - I Wayan Adi Pratama; Ni Desak Made Santi Diwyarthi (Westscience Press, 2024)
This study investigates the optimization of human resources (HR) and the utilization of information technology (IT) in driving the digital economy in Indonesia through a quantitative analysis. The digital economy has emerged as a transformative force reshaping industries, economies, and societies globally, with Indonesia positioned at the forefront of this digital revolution. However, the effective optimization of HR and IT remains critical for Indonesia to realize its full potential in the digital era. Through surveys and secondary data analysis, this research evaluates the current status of HR optimization and IT utilization, identifies influencing factors, and provides recommendations for policymakers and businesses. The findings offer valuable insights for fostering inclusive and sustainable digital development in Indonesia.